Properties of the likelihood ratio for semimartingales with deterministic triplets in the parametric case - Lin'kov, Yu. N.; Shevlyakov, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider semimartingales with deterministic discontinuous triplets. We obtain properties of the like-lihood ratio for the parametric case in terms of the Hellinger processes.